1990
DOI: 10.1139/x90-009
|View full text |Cite
|
Sign up to set email alerts
|

Foliar injury and growth response of red spruce to sulfate and nitrate acidic mist

Abstract: Seedlings of red spruce (Picearubens Sarg.) were exposed repeatedly, either in the field or in the greenhouse, to sulfuric acid mist, nitric acid mist (with or without ammonium ions), or a combination of sulfuric and nitric acid mist (with or without ammonium ions) for 10 to 39% of the time over periods of 6 to 19 weeks. Sulfuric acid mist produced visible foliar injury after repeated overnight exposures to pH 3 or less. Foliar symptoms were significantly less or absent after exposures to nitric acid or combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 0 publications
4
10
1
Order By: Relevance
“…Older (6-7-month-old) needles were more susceptible to injury from mist than current, elongating needles, as also found by Jacobson et al (19906), and bad niucb bigber sulphur levels after mist exposure tban new foliage. Tbese differences could be related to tbe smaller surface area of new needles exposed to mist or to cbanges in cuticular properties witb needle age.…”
Section: Effects Before Cold Acclimationsupporting
confidence: 55%
See 1 more Smart Citation
“…Older (6-7-month-old) needles were more susceptible to injury from mist than current, elongating needles, as also found by Jacobson et al (19906), and bad niucb bigber sulphur levels after mist exposure tban new foliage. Tbese differences could be related to tbe smaller surface area of new needles exposed to mist or to cbanges in cuticular properties witb needle age.…”
Section: Effects Before Cold Acclimationsupporting
confidence: 55%
“…Each seedling (48 or 56 per treatment) was rated for percent of needles showing necrotic lesions (i.e. incidence of foliar injury) with the following scale: 0 = 0%, l=less than 10%, 2 = 10-25%, 3 = 25-50%, 4 = 50-75 %, 5 = 75-90%, 6 = more than 90%, and 7 = 100% (Jacobson et al, 19906). One observer perfornned all ratings.…”
Section: Visible Injury Ratingmentioning
confidence: 99%
“…This study, coupled with previous work on acid mist exposures (Unsworth, 1984;Jacobson et al, 1990aJacobson et al, , b, 1992Sheppard et al, 19936), demonstrates the need for more emphasis to be placed on three specific areas of cloudwater exposure dy-namics: chemical composition of droplets on foliage at the end of cloud events, frequency of wet-dry cycles, and processes occurring during the drying of liquid on the foliage.…”
Section: Discussionsupporting
confidence: 51%
“…We previously reported that acidic mist can cause injury and abscission of red spruce needles and can alter shoot growth and foliar nutrient content (Jacobson et al, 1989;Jacobson et al, 1990a). Treatment with 16-hour intermittent exposures to high sulfate acidic mist with variation of mist acidity from event to event produced foliar injury in red spruce seedlings at median pH values as high as 3.5 (Jacobson et al, 19906).…”
Section: Introductionmentioning
confidence: 98%